DOI: 10.30707/etd2018.bruemmer.k
|View full text |Cite
|
Sign up to set email alerts
|

Voices Of Cooperating Teachers: Comparing Experiences Of Professional Development School And Traditional Student Teaching Models

Abstract: Further research also needs to examine the practitioner expertise held by the CT as a potential source of knowledge to inform the teacher preparation process. Specifically, it is important to understand the experience of CTs as they engage with the student teaching process. Additionally, to promote professional advancement for CTs, research needs to examine the effects of hosting a ST on the CTs' attitudes, teaching strategies, and participation in the organization and implementation of the student teaching pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Bruemmer (2018) investigated the practicing teachers’ experiences of working with teacher candidates in the PDS and non-PDS contexts. However, little evidence was found to support differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruemmer (2018) investigated the practicing teachers’ experiences of working with teacher candidates in the PDS and non-PDS contexts. However, little evidence was found to support differences.…”
Section: Resultsmentioning
confidence: 99%
“…For this current study, we identified 25 of the 210 dissertations that used a comparison methodology to provide a window into how learning in PDS and non-PDS settings may differ. Of these dissertations, 12 were quantitative (Anderson, 1995;Coffelt, 2013;Gissy, 2010;Grissom, 2003;Hahn, 2000;Hamar, 2013;Lancaster, 2010;Newsome, 2003;Ogletree, 2007;Poe, 2003;Ray, 2013;Van Holten, 2016); 11 used a mixed methods approach (Bruemmer, 2018;Curtain, 2006;Dadlez, 1998;Grieb, 2000;Hildreth, 1997;Komorek, 2013;Kuchinski, 2005;Malin, 2002;Patterson, 2004;Starling, 1999;Wright, 2009); and only two were qualitative in nature (Hopper, 2016;Miller, 2014). A few of the dissertations had findings that informed more than one category.…”
Section: Methods and Descriptive Analysis Of Dissertationsmentioning
confidence: 99%